Forage preference in two geographically co-occurring fungus gardening ants: A dietary DNA approach - Matthew Richards-Perhatch V; Elizabeth Boshers; Matthew Greenwold; Jon N. Seal (PLoS ONE, 2025)
Traditional methods of forage identification are impractical with non-leafcutting fungus gardening ants, making diet-related ecological and life history questions difficult to study. To address this limitation, we utilized dietary DNA metabarcoding on excavated ant fungus gardens to generate forage diversity metrics for the two co-occurring species Trachymyrmex septentrionalis and Mycetomoellerius turrifex . Ten fungus garden samples from each species were collected from a 60x70 m plot in East Texas. Each of the colonies we sampled was paired with a colony from the other species within 3 m of it. Plant forage diversity was assessed with chloroplast trnL primers, and insect frass forage diversity was assessed with mitochondria COI primers. DNA metabarcoding identified a total of 44 plant taxa across all samples, but performed poorly when characterizing foraged insect frass. Plant beta diversity was significantly different between the gardens of T. septentrionalis and M. turrifex colonies, as well as paired colonies. Colony pairs also had significantly different plant alpha diversity. This indicates that diet preference is likely driven both by ant species-specific plant preference, and colony location-specific plant resource availability. Overall, our results show that dietary DNA techniques are a promising tool for the identification of plant forage in ant fungus gardens, enabling the study of future diet-based ecological and natural history questions.